The Effectiveness of Criminal Sanctions in Stopping Smuggling of Lobster Seeds in Indonesia - Nining Yurista Prawitasari; Rad Cloud Dirgantoro Kesumojati (Dinasti Research, 2024)
Indonesia is a country that has wide seas separating one island from another, so smuggling can often occur considering the fact that Indonesia has very interesting marine products. Using illegal methods, marine biota becomes increasingly scarce, causing state losses of up to trillions of rupiah. The aim of this research is to find out the regulations regarding the prohibition of catching lobsters and the application of sanctions for the criminal act of smuggling lobster seeds. The research method used is normative juridical, this research was carried out by reviewing the applicable legislation and its application to a legal problem. The research specification used is the descriptive analysis method, namely a research method that describes phenomena or events based on existing facts, which is then linked to legal theory. Guidelines for catching lobster seeds are regulated in the Minister of Maritime Affairs and Fisheries Regulation Number: 16/PERMEN-KP/2022 concerning Management of Lobsters (Panulirus Spp.), Crabs (Scylla Spp.), and Crab (Portunus Spp.) in the Territory of the Republic of Indonesia.